Indexing aortic valve area by body surface area increases the prevalence of severe aortic stenosis. Issue 1 (22nd August 2013) - Jander, Nikolaus; Gohlke-Bärwolf, Christa; Bahlmann, Edda; Gerdts, Eva; Boman, Kurt; Chambers, John B; Egstrup, Kenneth; Nienaber, Christoph A; Pedersen, Terje R; Ray, Simon; Rossebø, Anne B; Willenheimer, Ronnie; et al.
Abstract : Background: To account for differences in body size in patients with aortic stenosis, aortic valve area (AVA) is divided by body surface area (BSA) to calculate indexed AVA (AVAindex ). Cut-off values for severe stenosis are <1.0 cm 2 for AVA and <0.6 cm 2 /m 2 for AVAindex . Objective: To investigate the influence of indexation on the prevalence of severe aortic stenosis and on the predictive accuracy regarding clinical outcome. Methods: Echocardiographic and anthropometric data from a retrospective cohort of 2843 patients with aortic stenosis (jet velocity >2.5 m/s) and from 1525 patients prospectively followed in the simvastatin and ezetimibe in aortic stenosis (SEAS) trial were analysed. Results: The prevalence of severe stenosis increased with the AVAindex criterion compared to AVA from 71% to 80% in the retrospective cohort, and from 29% to 44% in SEAS (both p<0.001). Overall, the predictive accuracy for aortic valve events was virtually identical for AVA and AVAindex in the SEAS population (mean follow-up of 46 months; area under the receiver operating characteristic curve: 0.67 (95% CI 0.64 to 0.70) vs 0.68 (CI 0.65 to 0.71) (NS). However, 213 patients additionally categorised as severe by AVAindex experienced significantly less valve related events than those fulfilling only the AVA criterion (p<0.001). Conclusions: Indexing AVA by BSA (AVAindex ) significantly increases the prevalence of patients with criteria for severe stenosis by including patients with a milder degree of the disease without improving the predictive accuracy for aortic valve related events.